PENDAPATAN USAHA KOPRA DI KECAMATAN SIPORA SELATAN KABUPATEN KEPULAUAN MENTAWAI: Income From Copra Business In South Sipora District, Mentawai Islands Regency - Alvindo Dermawan; Fransiskus Saroro; Syahrial; Muhammad Febriansyah Ibrahim (Jurnal AGRIBIS, 2026)
The most valuable portion of the coconut is its fruit since it can be used to make a variety of process good, including coconut sugar, oil, and white, hard coconut flesh, which may then be dried to produce a product with a respectable market value. This study set out to identify the features, profitability, and viability of copra enterprises in the Sipora Selataran District, as well as the traits of the copra business actors operating there.This study employed both qualitative and quantitative descriptive analysis. To choose respondents from the complete population, the Slovin technique was utilized, yielding a total of 26 respondents. The data analysis techniques employed include descriptive qualitative analysis, TKLK and TKDK cost analysis, copra business revenue, profit, R/C, B/C, and BEP analysis, which includes fixed and variable expenses as well as equipment depreciation costs. Among the traits of the copra industry actors in Sipora Selatan District are gender, age, experience, number of family dependents, land area, and education. Copra business actors in the South Sipora District make Rp. The BEP price is Rp 2,836.98, BEP production is 10,593 kg, and the B/C ratio of the copra company in South Sipora District is 2.54